2022
DOI: 10.1210/jendso/bvac041
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of the Heterogeneous Causes of Cushing Syndrome Resulting From Primary Macronodular Adrenal Hyperplasia (PMAH)

Abstract: Primary macronodular adrenal hyperplasia (PMAH) is considered a rare cause of adrenal Cushing’s syndrome, pituitary ACTH-independent, generally due to bilateral adrenal macronodules (>1 cm) and is often associated with variable cortisol secretion, resulting in a heterogeneous clinical presentation. Recent advances in the molecular pathogenesis of PMAH have offered new insights into the comprehension of this heterogeneous and complex adrenal disorder. Different molecular mechanisms involving the actors o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 72 publications
0
5
0
1
Order By: Relevance
“…In 2022, Vaczlavik et al [40] identi ed inactivating germline pathogenic variants in the lysine-speci c histone demethylase 1A gene (KDM1A) in BMAD patients diagnosed with food-dependent Cushing's syndrome and overexpression of the gastric inhibitory polypeptide receptor (GIP). Given that the authors detected no ARMC5 variations in those patients, such mutations appear to be mutually exclusive [40,41].…”
Section: Discussionmentioning
confidence: 84%
“…In 2022, Vaczlavik et al [40] identi ed inactivating germline pathogenic variants in the lysine-speci c histone demethylase 1A gene (KDM1A) in BMAD patients diagnosed with food-dependent Cushing's syndrome and overexpression of the gastric inhibitory polypeptide receptor (GIP). Given that the authors detected no ARMC5 variations in those patients, such mutations appear to be mutually exclusive [40,41].…”
Section: Discussionmentioning
confidence: 84%
“…The ARMC5 gene was found to be the major genetic cause of PMAH and included nearly 80% of familial cases with PMAH and 30% of apparently sporadic forms [ 4 , 12 ]. ARMC5 has germline and somatic mutations, according to genetic analysis [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, mutations in tumor suppressor genes, such as adenomatous polyposis coli gene ( APC ), menin ( MEN1 ), fumarate hydratase ( FH ), and armadillo repeat-containing protein 5 ( ARMC5 ), which later is detected in 20% to 50% of PMAH cases [ 8 ]. Recently, the other tumor suppressor gene, lysine (K)-specific demethylase 1A ( KDM1A) was identified in PMAH associated with food-dependent Cushing’s syndrome [ 9 , 10 , 11 , 12 ]. Furthermore, mutations in the ACTH receptor gene and guanine nucleotide-binding protein alpha-stimulating activity polypeptide ( GNAS ), cAMP-dependent protein kinase catalytic subunit alpha ( PRKACA ), phosphodiesterase 11A ( PDE11A ), and phosphodiesterase 8B ( PDE8B ) less frequently occurred in patients [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…These authors argue that more than one aberrant receptor is identified in each patient, rendering it difficult to select a specific receptor to be blocked (10) and that the use of aberrant receptor antagonists does not usually allow long-term control of hypercortisolism. Moreover, they are expensive and time-consuming tests (43). Nevertheless, the evaluation of the presence of aberrant receptors offers the possibility of using specific drugs to block the identified aberrant hormone receptors.…”
Section: Study Of Aberrant Receptorsmentioning
confidence: 99%